Effect of insecticide-treated bed net usage on under-five mortality in northern Ghana - Afoakwah, C.; Nunoo, J.; Andoh, F.K. (Malaria Journal, 2015)
Although under-five mortality rate seems to be declining in Ghana, the northern part of the country has higher levels of under-five mortality vis-à-vis the national rates. This research examines the correlates of the high under-five mortality among children in the northern part of Ghana, with emphasis on the usage of insecticide-treated bed net (ITN), as recommended by the World Health Organization. A total of 3,839 under-five children sourced from the Ghana Demographic and Health Survey-was used for this study. Univariate descriptive statistics was employed to describe the variables used for the empirical estimation. The maximum likelihood estimation technique was used to estimate a logit model in other to determine the effect of insecticide treated bed net usage on under-five mortality. Insecticide-treated bed net usage among children enhances their survival rates. Thus, under-five mortality among children who sleep under treated bed nets is about 18.8% lower than among children who do not sleep under treated bed nets. While health facility delivery was found to reduce to reduce under-five mortality, child bearing among older women is detrimental to the survival of the child. The study, therefore, recommends that policies targeting reduction in under-five mortality in northern Ghana should consider not mere availability of ITNs in the household, but advocate the usage of these treated nets. The study recommends to the Ministry of Health to extend their services to unreached rural communities to encourage health facility delivery to reduce under-five mortality (PDF) Effect of insecticide-treated bed net usage on under-five mortality in northern Ghana. Available from: https://www.researchgate.net/publication/280868825_Effect_of_insecticide-treated_bed_net_usage_on_under-five_mortality_in_northern_Ghana [accessed Sep 12 2018].
Keywords: ITN usage; Under ﬁve mortality; Health facility delivery; Northern Ghana